Unlocking the therapeutic potential of Saussurea costus: purification and functional characterization of α-amylase inhibitors - Ben Abdelmalek, Imen; Alhmdi, Tomather A. A.; Ben Bacha, Abir; Krayem, Najeh (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionRegulating the catalytic activity of alpha-Amylase enzymes can decrease glucose production during the postprandial phase, potentially offering therapeutic benefits for diabetes. This research aimed to assess the inhibition of α-amylase using crude extracts from Saussurea costus, a medicinal plant traditionally used for treating diabetes and its associated complications.MethodsTwo novel potent proteinaceous amylase inhibitors: ScAI-R and ScAI-L were purified and characterized from Saussurea costus roots and leaves.ResultsThe pure inhibitors exhibited an apparent molecular weight of about 16 kDa and a high N-terminal sequence identity (81%) with the monomeric α-amylase inhibitors from Kengyili amelanthera and Triticum dicoccoides. In addition to their significant stability at extreme pH values (2.0–12.0) and temperatures (100°C), the structural integrity of both inhibitors was remarkably enhanced in the presence of divalent cations such as Mg2+, Ca2+, and Hg2+ at 5 mM. Interestingly, the half-maximal inhibitory concentrations of ScAI-R (IC50 = 23 μg/mL) or ScAI-L (IC50 = 28 μg/mL) against human salivary amylase against were comparable to that of the standard drug acarbose (IC50 = 23 μg/mL). Both purified inhibitors acted as non-competitive inhibitors with Ki values of 0.38 and 0.32 µM, respectively, and displayed the highest affinities towards human salivary and pancreatic α-amylases (up to 90% inhibitory activity) and, to a lesser extent, porcine pancreatic α-amylase (∼70% inhibitory activity). Furthermore, these inhibitors exhibited efficient antimicrobial activities against Gram (−) and Gram (+) bacteria, as well as fungal strains. Cytotoxicity towards the human cancer colorectal cells LoVo and HCT-116 with an IC50 of up to 50 μg/mL was also observed.DiscussionThus, Saussurea costus α-amylase inhibitors could be potential candidates for hyperglycemic control in diabetic and colorectal cancer patients.